A conceptual model of supra‐glacial lake formation on debris‐covered glaciers based on GPR facies analysis. Issue 6 (29th November 2016) - Mertes, Jordan R.; Thompson, Sarah S.; Booth, Adam D.; Gulley, Jason D.; Benn, Douglas I.
Abstract: Supra‐glacial lakes and ponds can create hotspots of mass loss on debris‐covered glaciers. While much research has been directed at understanding lateral lake expansion, little is known about the rates or processes governing lake deepening. To a large degree, this knowledge gap persists due to sparse observations of lake beds. Here we report on the novel use of ground penetrating radar (GPR) surveys to simultaneously collect supra‐glacial lake bathymetry and bottom composition data from Spillway Lake (surface area of 2.4 × 10 5 m 2 ; volume of 9.5 × 10 4 m 3 ), which is located in the terminus region of the Ngozumpa Glacier in the Khumbu region of the Nepal Himalaya. We identified two GPR bottom signals corresponding to two sedimentary facies of (1) sub‐horizontal layered fine sediment drape and (2) coarse blocky diamict. We provide an understanding of the changes in subaqueous debris distribution that occur through stages of lake expansion by combining the GPR results with in situ observations of shoreline deposits matching the interpreted facies. From this, we present an updated conceptual model of supra‐glacial lake evolution, with the addition of data on the evolving debris environment, showing how dominant depositional processes can change as lakes evolve from perched lakes to multi‐basin base‐level lakes and finally onto large moraine‐dammed lakes. Throughout lake evolution, processes such as shoreline steepening, lakebed collapse into voids and conduit interception, subaerial and subaqueous calving and rapid areal expansion alter the spatial distribution and makeup of lakebed debris and sediments forcing a number of positive and negative feedbacks on lake expansion. Copyright © 2016 John Wiley & Sons, Ltd.